Pain Management Services in Hospital: The Human’s Right to Health Services - Jaya, A A Gde Putra Semara; Yustina, Endang Wahyati; Kuntjoro, Tjahjono (Soepra Jurnal Hukum Kesehatan, 2024)
Pain is suffering for the patient and must be treated immediately. Health professionals need to recognize, assess, understand, and treat pain. Pain management services have not been run optimally in several hospitals. Pain management services are an effort to fulfill the right to health services. This research aims to observe the implementation of pain management services to fulfill the right to health services, especially at the Mangusada Hospital of Badung Regency, Bali, Indonesia. The research method used in this study is the socio-legal approach (empirical legal study) with explanatory specifications. This research was conducted in 2023 as a case study. Primary and secondary data were collected through field and literature studies. Analysis was performed on qualitative and quantitative data. We found that 1) pain management services in Indonesian have legal bases with general and specific technical regulations at the national level, but the specific technical regulations at the Mangusada Hospital are not up-to-date, comprehensive, and harmonious, 2) Mangusada Hospital and its health professionals have not been optimal in providing pain management services to fulfill the right to health services, in terms of the comprehensive legal instruments, the organization of health professionals, and the availability of infrastructure and facilities. Breach of obligations by hospitals and health professionals can be seen as a failure to provide essential services and reduce suffering, substandard service, negligence, a breach of the patient’s human rights, and have legal implications, and 3) legal, social, and technical factors influence the implementation of pain management services in Mangusada Hospital.